FLAME PROFILE IN A POROUS RADIANT BURNER USING 1/2” AND 1/4” ALUMINA’S SPHERES - Campos, G. P. L.; Duarte, J. B. F. (Revista de Engenharia Térmica, 2018)
Porous burners are known by their high efficiency and low polluting gases emissions. Their high efficiency is given by the great thermal radiation potential, whereas differently a normal burner, the process of combustion happens in the inner of the porous medium, which is compound by spheres of alumina, and the mix air-fuel goes through the preheating zone, potentializing the combustion. The burners are usually used in the industry, in the process of drying of paper and wood, plastic coating, food cooking and ambient heating. In this article, it was studied the behaviour of the flame in a porous radiant burner with alumina’s sphere of 1/2” and 1/4”, using LPG as fuel, compressed air as oxidizing agent and ceramic wool as thermal insulation. The burner was divided in three essential sections with a type K thermocouple in each one, which are: base, middle and top. The flame profile encountered was a floating one, however it is almost stable, presenting low variations of temperature and according to previously tests, less consuming of fuel.